Plata y sociedad regional. Reales de minas pequeños en la Nueva España, siglos XVI – XVIII: Entre lo rural y lo urbano - Brígida von Mentz (Nuevo mundo - Mundos Nuevos, 2015)
This essay deals with the small mining centers like Sultepec, Taxco and others, located south of Mexico City, during the Colonial period; some were located far from the main trading routes. The marginality is described, the social inequality, the importance of the miner- ranchers, and the way the mining enterprises used the native inhabitants as local suppliers. The social and political context permitted the rentability of the mining enterprises lowering the costs of some salaries and local products. This essay proposes that the idea that the mining industry was the “motor of the economy” has to be analyzed with care, considering those sectors that were benefited and those who were not.